2011
DOI: 10.1186/1471-2407-11-19
|View full text |Cite
|
Sign up to set email alerts
|

Classical homeopathy in the treatment of cancer patients - a prospective observational study of two independent cohorts

Abstract: BackgroundMany cancer patients seek homeopathy as a complementary therapy. It has rarely been studied systematically, whether homeopathic care is of benefit for cancer patients.MethodsWe conducted a prospective observational study with cancer patients in two differently treated cohorts: one cohort with patients under complementary homeopathic treatment (HG; n = 259), and one cohort with conventionally treated cancer patients (CG; n = 380). For a direct comparison, matched pairs with patients of the same tumour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0
11

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 32 publications
2
38
0
11
Order By: Relevance
“…Many cancer patients are now treated with complementary and alternative medicine (CAM) for its less toxic side-effects. Different preparations of herbal extracts including homeopathy are some of the most popular CAM modalities for cancer patients in seven out of 14 European countries today (Rostock et al, 2011). However, many of these herbal extracts used as homeopathic mother tinctures have not been scientifically validated.…”
Section: Introductionmentioning
confidence: 99%
“…Many cancer patients are now treated with complementary and alternative medicine (CAM) for its less toxic side-effects. Different preparations of herbal extracts including homeopathy are some of the most popular CAM modalities for cancer patients in seven out of 14 European countries today (Rostock et al, 2011). However, many of these herbal extracts used as homeopathic mother tinctures have not been scientifically validated.…”
Section: Introductionmentioning
confidence: 99%
“…'Classical' homeopathy employs highly diluted remedies, whereas 'complex' homeopathy uses combinations of dilute agents for specific clinical conditions. Usually, the patients use it for symptomatic relief and general supportive care, as well to reduce side effects of treatments [45,46].…”
Section: Homeopathymentioning
confidence: 99%
“…The conventionally treated group had no improvement in one QOL scale after three months and a slight improvement in the other QOL scale; at twelve months there was a slight increase in one indicator and a decrease in the other. Fatigue and anxiety/depression were not improved in the conventionally treated group; fatigue but not anxiety/depression improved in the homeopathy group (Rostock, et al, 2011). A meta-analysis of all clinical studies on cancer treatment outcomes using homeopathy (Milazzo et al, 2006) found that all studies examined were investigating the use of homeopathy for adjunctive symptom treatment, not as primary antitumor treatment.…”
Section: Cancer and Homeopathymentioning
confidence: 99%